Structural Capital Development and Intra-Organizational Integration of Premium Restaurants In Rivers State, Nigeria - Judipat Nkiru , Obiora, (International Journal of Scientific Research and Management (IJSRM), 2021)
The imperatives of intraorganizational integration anchor on the establishment of systemic features necessary for organizational effectiveness and efficiency. Such outcomes border on the support and framework advanced by the structural components of the organization, and the extent to which infrastructures and norms serve the goal of improved service quality and delivery especially within the hospitality industry. This paper identified structural capital development as a significant predictor of intraorganizational integration (communication and knowledge sharing) in premium restaurants in Rivers State – thus, reinforcing the institutional theory on the criticality of learning and the embodiment of external values and considerations in shaping or defining organizational structures, routines and policies. The findings however indicate that structural capital does not influence cohesion within the premium restaurants. In conclusion, emphasis is placed on the imperatives of informed change activities channelled towards organizational infrastructure and functions; such that anchor on the unique characteristics or attributes of the environment; thus enabling a more harmonic and systemic outcome for the internal as well as external features of the organization